Inguinal hernia in southern Brazil - challenges in follow-up and recurrence rates - RODRIGO PILTCHER-DA-SILVA; DEBORA OLIVEIRA HÜTTEN; ARTUR GEHRES TRAPP; PEDRO SAN MARTIN SOARES; TIAGO LIMA CASTRO; SIMONI BOHNENBERGER; EDUARDO CASTELLI KROTH; JORGE ARMANDO REYES PINTO; CAROLINE GREHS; DANIELLE CRISTINA TOMASI; LEANDRO TOTTI CAVAZZOLA (Revista do Colégio Brasileiro de Cirurgiões, 2022)
ABSTRACT Introduction: recurrence rates for primary hernia repair range from 0.5 to 15 percent depending upon the hernia site, type of repair, and clinical circumstances. Many risk factors are known and they must be considered before the procedure. In developing countries, follow up and maintenance of databases are critical to understand the real numbers. Methods: a retrospective cohort study analyzed adult patients who have undergone inguinal hernia repair at Hospital de Clínicas de Porto Alegre, a tertiary care government public hospital, between 2013 and 2015. Medical records, telephone, and letter contact have been reviewed in order to complete the minimum period of 5 years of follow-up. The analyzed data focused on the surgeon’s experience and the recurrence rate in 5 years of follow-up. Results: a total of 1094 medical records were selected and a complete five years follow-up were possible in 454 patients - 538 inguinal hernia repairs due to bilateral approach in 84 patients. These 454 patients answered, in a validated questionnaire about symptoms of recurrence. The total recurrence rate was 9.29%. For the patients who had Nyhus IV, recurrence rate was 24.1% against 9.9% after primary hernia repair, with a 2.4 higher risk. There was no difference in recurrence between surgeons and training surgeons. Conclusion: our data reveal an acceptable recurrence rate in a tertiary care hospital with residents, and to our knowledge is the first Brazilian report with long term follow up. An increased re-recurrent hernia was found when compared with primary hernia repair.